Políticas Educacionais da Secretaria Municipal de Educação de Santarém no Período de 2003 a 2016 - GOCH, Greice Jurema de Freitas (Universidade Federal do Oeste do Pará, 2021)
The research aimed to identify and record the educational policies implemented by the Municipal Department of Education and Sports of Santarém, state of Pará, from 2003 to 2016. The choice of the period to conduct the research was based on the survey of production educational policy in the education secretariats. The regulatory and historical frameworks that influenced the formulation of the Brazilian educational policy, such as the Law of Directives and Bases of Education, Law 9,394 of December 20, 1996, the Law of FUNDEB, Law No. 11494/2007, were adopted. (2002), Azevedo (2001), Perez (2010), Draibe and Riesco (2011), which relate social policy to public policy. And other more specific ones about the approach of educational policy, among them: Martins (2002), Ganzeli (2013), Gouveia (2013), Colares and Colares (2013), Santos (2014), Carneiro and others. It presents the panorama of education in Santarém and the educational policies implemented by the Municipal Secretary. In the methodology the qualitative research was adopted, having as category of analysis: programs, projects and actions developed by the Secretary of Education. In the production of data, bibliographical research and documentary analysis were used, having as sources: Municipal plans of education; Democratic management law; Career and Compensation Plan; Plan of articulated actions (PAR); the Organic Law of the municipality; management reports; information, among others. The results show that municipal education policies are related to federal programs, as well as interference with the socioeconomic context in the elaboration of legislation, which can be verified with the Law on Guidelines and Bases of National Education - Law 9394/96 and National Education Plan - Law 13.005 / 2014, among others. Emphasizing the category of analysis of programs, projects and actions, it was noticed that most of these programs, from 2003 to 2016, were instituted and implemented policies of the microsystem for the microsystem. Progress has been made in improving educational indicators; investments in teacher training and qualification through partnerships with university institutions; establishment of agreements with federal programs and projects through the FNDE for the construction of buildings; extensions, reforms of municipal schools. On the other hand, there were some setbacks caused by the discontinuation of local programs, projects and actions.